Analysis of the Main Financial and Stock Market Indicators of a Sports Equipment Manufacturing Company - Bogdan Cosmin GOMOI (CECCAR Business Review)

(untitled)
Companies with international visibility, listed on the stock exchange and with a long history on the market have gradually evolved and enjoy prestige, acquired as a consequence of the quality, innovative character, and diversity of the products and services offered. Nike company, founded in the United States of America in the early 1970s, stands out as one of the largest manufacturers of sports equipment worldwide. Nike brand is distinguished by its iconic symbol, the Swoosh, one of the most famous logos, and by the motto “Just Do It”, one of the most used motivational slogans. Financial indicators are rates that inform users about the financing structure and its allocation, the ability to pay debts, the dynamics of the operating cycle or the performance obtained. Stock market indicators are price multipliers/indices that relate the market price of companies’ shares to various factors corroborated with it, such as profit per share, turnover per share, book value of a share or cash flow per share.